HISTOPATHOLOGICAL INSIGHTS INTO EARLY-STAGE COLORECTAL CANCER: A COMPARATIVE STUDY OF MORPHOLOGICAL FEATURES, MOLECULAR MARKERS, AND CLINICAL IMPLICATIONS - Dr Sidra Javed; Dr Madiha Ehsanulhaq; Dr Sahar Iqbal; Dr Hira Ajmal Rana; Dr Rabia Afzal Malik; Dr Mehwish Niazi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: To elucidate the relationship between histopathological features, molecular markers, and clinical outcomes in early-stage colorectal cancer (CRC).Methods: A comparative study involving 185 patients diagnosed with early-stage CRC. Data were collected retrospectively, including demographic information, histopathological features (tumor grade, glandular formation, stromal response), molecular markers (MSI status, KRAS and BRAF mutations), and clinical outcomes (recurrence, metastasis, overall survival). Statistical analyses included Chi-square tests, T-tests, Kaplan-Meier survival analysis, and Cox proportional hazards models.Results: The study found that poorly differentiated tumors had higher recurrence (25%) and metastasis (15%) rates compared to well-differentiated (7.1% and 2.9%, respectively) and moderately differentiated tumors (21.1% and 10.5%). MSI-High patients showed lower recurrence (12.5%) and metastasis (5%) rates than MSS patients (17.2% and 9%). KRAS and BRAF mutations were linked to increased recurrence (16.7% and 20%) and metastasis (8.3% and 12%). Absence of glandular formation and severe stromal response were associated with higher recurrence (28.6% each) and metastasis rates (14.3% each).Conclusions: Comprehensive histopathological and molecular evaluation is crucial in predicting clinical outcomes in early-stage CRC. Poor tumor differentiation, absence of glandular formation, severe stromal response, and presence of KRAS and BRAF mutations are significant prognostic indicators.